Phase III, efficacy and safety study of ertugliflozin monotherapy in people with type 2 diabetes mellitus inadequately controlled with diet and exercise alone. Issue 5 (22nd February 2017) - Terra, Steven G.; Focht, Kristen; Davies, Melanie; Frias, Juan; Derosa, Giuseppe; Darekar, Amanda; Golm, Gregory; Johnson, Jeremy; Saur, Didier; Lauring, Brett; Dagogo‐Jack, Sam
Abstract : Aims: To conduct a phase III study to evaluate the efficacy and safety of ertugliflozin monotherapy in people with type 2 diabetes. Materials and methods: This was a 52‐week, double‐blind, multicentre, randomized, parallel‐group study with a 26‐week, placebo‐controlled treatment period (phase A), followed by a 26‐week active‐controlled treatment period (phase B) in 461 men and women, aged ≥18 years with inadequate glycaemic control (glycated haemoglobin [HbA1c] concentration 7.0% to 10.5% [53‐91 mmol/mol], inclusive) despite diet and exercise. Results from phase A are reported in the present paper. The primary endpoint was the change in HbA1c from baseline to week 26. Results: At week 26, the placebo‐adjusted least squares mean HbA1c changes from baseline were −0.99% and −1.16% for the ertugliflozin 5 and 15 mg doses, respectively ( P  < .001 for both doses). The odds of having HbA1c <7.0% (53 mmol/mol) were significantly greater in the ertugliflozin 5 and 15 mg groups compared with the placebo group. Both doses of ertugliflozin significantly lowered fasting plasma glucose and 2‐hour postprandial glucose levels and body weight. The placebo‐adjusted differences in changes from baseline in systolic blood pressure were not statistically significant. A higher incidence of genital mycotic infections occurred in men and women treated with ertugliflozin compared with placebo. There was no significant difference between treatments in the proportion of participants with symptomatic hypoglycaemia or adverse events associated with urinary tract infection or hypovolaemia. Conclusions: Ertugliflozin 5 and 15 mg treatment for 26 weeks provides effective glycaemic control, reduces body weight and is generally well tolerated, when used as monotherapy.